KUALITAS DENDENG IKAN SELAR (Selaroides leptolepis) DENGAN PENAMBAHAN LIKOPEN DARI TOMAT (Lycopersicum pyriforme) - Elfirah, Elfirah (JSTT, 2015)
The aimof the research was to study about the influence of tomato lycopene concentrates and stronge duration on chemical quality and organoleptic of jerked yellowstripe scad. Storage durations used for the exsperiments were 0,2,4 and 6 weeks, and licopene concentratious were 0,10,20,30,40 and 50%. Quality of the jerked yellowstripe scad oserved were colour, tenderuess, flavor and founduess. Preokside numbers, water content, fat content and licopene werw characterized to obtain its nutritious values. Laboratory results showed that for 6 weeks storage had peroxide number 30,03 mg and the best addition of licopene 0% around 18,13 mg. Water content with 6 week sorage was 23,81 mg and the best licopene 50% addition was 23,33 mg, the best fat content of 0 week sorage was 6 mg and the highest licopene addition of 0% was 5, 56 mg, the highest licopene level with 0 week storage was 0,09 mg and addition of storage duration and licopene addition sufluenced scores of colour and tenderuess; but those did not affect scores of flavor and founuess. Mostly pauclists scored the jerked yellowstripe scad that was the most preferred from the side of colour (score 3,37) for the L2 sampels. Tenderuess of the jerked fish with the best licopene addition was 3,93 for the L3 samples. The flavor with licopene addition was found 3,77 for the L2 samples. Founduess for the jerked fish licopene addition was 3,12 for the L5 samples.Â